Feminist Collections, v.10, no.2 (winter 1989) - (:unkn) unknown (My University, 1989)
Subtitle: A Quarterly of Women's Studies Resources. 22p.
FEMINIST VISIONS: Four pioneer women filmmakers. NEWS FROM UW-RIVER FALLS. WISCONSIN'S OWN "MOTHER COURAGE" PRESS. NEW REFERENCE WORKS IN WOMEN'S STUDIES: New sources on women of color, voluntary organizations, North American women, biographies around the world, American women's speeches, reproductive rights, abortion, the changing family, British women writers, and alternative publishers of children's books. PERIODICAL NOTES: New periodicals on disabled women; South Asian women; ethnic women; child sexual abuse survivors; gay and lesbian psychotherapy; women's studies (NWSA); and women mariners. Special issues on new scholarship on gender; women workers; women managers; career counseling; moral education and development; magazines by and for women; gender, text and meaning; women in public relations; Black men and women; gender and aging; and a symposium on women's studies. Transitions: Sojourner has a new address. Ceased publication: Outwrite Women's Newspaper. ITEMS OF NOTE: A series on Canadian women writers; an international women's database; a rare book dealer in women's literature and culture; and a guide for career planning with disabled women and girls. WISCONSIN BIBLIOGRAPHIES IN WOMEN'S STUDIES: The second printing of a bibliography on women and the history of science. BOOK REVIEWS: Women's political participation: A current look at promise and constraints, by Georgia Duerst-Lahti. A potpourri of spiritual experience, by Ellie Amico. Women and AIDS, by Cara Hoffert. BOOKS RECENTLY RECEIVED.
Keywords: Women's Studies; Gender; Feminism; Library Resources; Reviews